2014
DOI: 10.1371/journal.pone.0107502
|View full text |Cite
|
Sign up to set email alerts
|

A Novel miR-451a isomiR, Associated with Amelanotypic Phenotype, Acts as a Tumor Suppressor in Melanoma by Retarding Cell Migration and Invasion

Abstract: miRNAs are key regulatory small non-coding RNAs involved in critical steps of melanoma tumorigenesis; however, the relationship between sequence specific variations at the 5′ or 3′ termini (isomiR) of a miRNA and cancer phenotype remains unclear. Deep-sequencing and qRT-PCR showed reduced expression of miR-144/451a cluster and most abundant isomiR (miR451a.1) in dysplastic nevi, in-situ and invasive melanomas compared to common nevi and normal skin (n = 101). miRNA in situ hybridization reproducibly confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Isoforms of miR differ slightly from mature miR by base length and sequence and are referred to as isomiR. Although the function of isomiR is not completely understood, they are known to play an important role in cancer development [18,19]. IsomiRs also exist in the blood with high stability, similarly to mature miRs.…”
Section: Introductionmentioning
confidence: 99%
“…Isoforms of miR differ slightly from mature miR by base length and sequence and are referred to as isomiR. Although the function of isomiR is not completely understood, they are known to play an important role in cancer development [18,19]. IsomiRs also exist in the blood with high stability, similarly to mature miRs.…”
Section: Introductionmentioning
confidence: 99%
“…18 miR-211 functions as a metabolic switch 19 and as a potent tumor suppressor in vitro influencing gene pathways involved in cell invasion. [20][21][22] It is located within the noncoding sequence (intron 6) of Melastatin-1 (MLSN-1) gene, 20 which is expressed at high levels in melanocytic nevi but significantly reduced in metastatic melanomas with variable expression in primary lesions. 23 Loss of MLSN-1 mRNA is predictive of significantly reduced disease-free survival of melanoma patients.…”
mentioning
confidence: 99%
“…Babapoor and team [44] identified isomiR sequence of miRNAs that were deregulated in cutaneous melanomaand found that miR-451a was functioning as a tumor suppressor in gastrointestinal cancer cells and glioma cells. They concluded that miR-451a was involved in melanoma progression while the mature form of this isomiR, miR-451a.1 was associated with amelanotic melanoma [44]. Zhang and coworkers [45] developed a new method to discover the catalogue of isomiRs in association with cancer progression in human.…”
Section: Role Of Isomirs In Human Diseasesmentioning
confidence: 99%